Simulation study on electromagnetic characteristics of Halbach-Array Dual-Permanent-Magnet excited vernier machine - Xiuping Wang; Changhua Wang; Chunyu Qu (Energy Reports, 2023)
In order to further improve the output performance of the motor, a new Halbach-array Dual-Permanent-Magnet Excited Vernier Machine (HA-DPMVM) applied to the direct drive system of electric vehicles is designed in this paper. Firstly, the topology of HA-DPMVM motor is introduced, and a reasonable armature winding distribution is designed according to its structural characteristics, so that two groups of permanent magnets on the stator and rotor are coupled with the armature winding at the same time; Secondly, the working principle is analyzed, and the permanent magnetic field generated by the two groups of permanent magnets is modulated into effective harmonic magnetic field by using the bidirectional modulation effect of stator and rotor teeth on the air gap permeance; Finally, the no-load air gap magnetic density, no-load back EMF, cogging torque and output torque of the motor when only the rotor permanent magnet is excited, only the stator permanent magnet is excited and the stator and rotor permanent magnets are excited simultaneously are analyzed and compared by the finite element method. The simulation results show that compared with the conventional permanent magnet vernier motor, the new motor has significant advantages in magnetic circuit performance, no-load performance and steady-state performance, and its comprehensive performance is better.